2013
DOI: 10.1111/cei.12210
|View full text |Cite
|
Sign up to set email alerts
|

Natural killer (NK) cell deficit in coronary artery disease: no aberrations in phenotype but sustained reduction of NK cells is associated with low-grade inflammation

Abstract: SummaryAlthough reduced natural killer (NK) cell levels have been reported consistently in patients with coronary artery disease (CAD), the clinical significance and persistence of this immune perturbation is not clarified. In this study we characterized the NK cell deficit further by determining (i) differentiation surface markers and cytokine profile of NK cell subsets and (ii) ability to reconstitute NK cell levels over time. Flow cytometry was used to analyse NK cell subsets and the intracellular cytokine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 35 publications
3
38
0
5
Order By: Relevance
“…Another study reported decreased NK cells in patients at the time of diagnosis. Furthermore, a 12-month follow-up showed that a continued deficient in NK cells was correlated with low-grade cardiac inflammation, whereas patients that had restored circulating NK cells had little to no cardiac inflammation [65, 66]. …”
Section: Heart Disease Accompanied By Inflammationmentioning
confidence: 99%
“…Another study reported decreased NK cells in patients at the time of diagnosis. Furthermore, a 12-month follow-up showed that a continued deficient in NK cells was correlated with low-grade cardiac inflammation, whereas patients that had restored circulating NK cells had little to no cardiac inflammation [65, 66]. …”
Section: Heart Disease Accompanied By Inflammationmentioning
confidence: 99%
“…Other studies indicate that patients with severe atherosclerosis have greater numbers of circulating NK cells (Clerc and Rouz, ); elderly patients with peripheral artery disease also have greater numbers of circulating NK cells but with reduced cytotoxic capability (Bruunsgaard et al, ). Immediately after non‐STEMI MI NK cell numbers are low and then increase over the ensuing 12 months possibly contributing to MI‐accelerated atherosclerosis; their failure to increase in some patients is associated with persistent low‐grade inflammation (Backteman et al, ). In other studies, circulating but not lymph node CD56+ NK cells are reduced in patients with acute coronary syndrome compared with patients with stable angina (Backteman et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Expression of NK cell sensors was also decreased in MI (68). A recent study reported that chronic NK cell deficiency was associated with low-grade chronic inflammation, which indicates a protective role for NK cells in atherosclerosis and MI healing (72).…”
Section: Lymphocyte Diversity In MImentioning
confidence: 83%